Perspectives on Community Well-Being - Kee, Youngwha; Lee, Seung Jong.; Phillips, Rhonda; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume brings together multiple diverse perspectives from around the globe on quality of life and community well-being from a place-based perspective. It provides both conceptual and applied explorations across disciplines, ideas and perspectives to foster more interest and research in community well-being. Topics include surveying at the community level, child friendly communities, collective impact, grieving, and happiness. Those working in the areas of public policy, community development, community and social psychology, as well as planning and development will find this volume particularly useful for the array of perspectives, research, and analytical approaches presented. .
Chapter 1. Measuring Happiness: A Practical Review; Kai Ludwigs, Lena Henning and Lidia R. Arends -- Chapter 2. An Indigenous Perspective on Quality of Life; Pat Lauderdale -- Chapter 3. A Participatory Process: Creating Child Friendly Environments in Immediate Surroundings; Ümran Topcu and Şebnem Cana Kacar -- Chapter 4. Community Well-Being and Migration Intention of Residents; YeonKyeong Lee and Seung Jong Lee -- Chapter 5. Perceived Social Support Systems for Bereaved Students in Walter Sisulu University: A Pilot Study; Sabine Baninzi and T. Mdleleni-Bookholane -- Chapter 6. Community Well-being Data Collection Methodology, The case of Enschede, the Netherlands; Javier Martinez and Frans van den Bosch -- Chapter 7. The Relationship Between the Types of Needs Satisfaction and Subjective Well-being; Young Woong Kang and Seung Jong Lee -- Chapter 8. Shredding the Evidence: Whose Collective Impact are we talking about?; Geoffrey Woolcock -- Chapter 9. Fiscal Structure and Residents' Well-Being in Korea; Youngkyun Oh -- Chapter 10. Arts and Community Well-Being; HeeKyung Sung -- Chapter 11. Spirituality: The Missing Link of Sustainability and Happiness: A Framework for Holistic Development; Erica Berejnoi, Rohana Ulluwishewa, Scott Cloutier, Leah Gibbons and Susana Puga. .
Keywords: Quality of life; Community psychology; Social policy; Quality of Life Research; Community Psychology; Social Policy